Party Foot-Soldiers, Quasi-Militias, Vigilantes, and the Spectre of Violence in Zimbabwe’s Opposition Politics - Charles Moyo (Modern Africa, 2020)
Scholarship tends to neglect the phenomenon of political violence in opposition parties in Zimbabwe. The prevailing narrative is that political violence is largely a monopoly of the state and the ruling party, Zimbabwe African National Union – Patriotic Front (ZANU-PF). However, an emerging trend implicates opposition political parties, particularly the Movement for Democratic Change (MDC). The MDC’s party’s foot-soldiers, especially the “Vanguard,” often exhibit violent tendencies. Accordingly, the present article explores the scourge of intra-party violence in the opposition party MDC between 2005 and 2019. The article conceptualises and contextualises MDC’s violence through the lenses of Zimbabwe’s political culture and socialisation in the context of the country’s pre-colonial, colonial, and postcolonial historical trajectories.